The cost‐effectiveness of dapagliflozin compared to DPP‐4 inhibitors in the treatment of type 2 diabetes mellitus in the Netherlands. Issue 4 (18th September 2020) - Van der Linden, N.; Van Olst, S.; Nekeman, S.; Uyl‐de Groot, C.A.
Abstract: Aim: When glycaemic control for people with type 2 diabetes is not achieved with metformin and sulfonylurea alone, adding another oral anti‐diabetes drug, such as a sodium–glucose co‐transporter 2 (SGLT2) or dipeptidyl peptidase‐4 (DPP‐4) inhibitor, is an alternative to starting insulin. The aim of this study is to determine the cost‐effectiveness of dapagliflozin (an SGLT2 inhibitor) compared with DPP‐4 inhibitors when added to metformin and sulfonylurea in people with type 2 diabetes in the Netherlands. Methods: A cost–utility analysis is performed using the Cardiff diabetes model, a fixed‐time increment stochastic simulation model informed by 'United Kingdom Prospective Diabetes Study 68' risk equations. The base‐case analysis uses a 40‐year time horizon, a Dutch societal perspective and differential discounting (4% for costs, 1.5% for effects). Inputs are obtained from the literature and Dutch price lists. Univariate and probabilistic sensitivity analysis are performed. Results: Dapagliflozin is dominant compared with DPP‐4 inhibitors, resulting in a €990 cost saving and a 0.28 quality‐adjusted life year gain over 40 years. Cost savings are associated mainly with treatment costs and a reduced incidence of micro‐ and macrovascular complications, among others nephropathy, myocardial infarction and stroke. Results are robust to changes in input parameters. Conclusions: Dapagliflozin is a cost‐saving alternative to DPP‐4 inhibitors when added to metformin and sulfonylurea. The incidence of micro‐ and macrovascular complications is lower for people treated with dapagliflozin. Uncertainty around this outcome is low.